Land covers monitoring for Bahar-Al-Najaf (Iraq) based on sentinel-2 imagery - Al-Helaly, Mustafa Hasan; Alwan, I. A.; Al-Hameedawi, Amjed Naser (Journal of physics. Conference series, 2021)
the last four years have seen a remarkable rise in water levels to the Bahar-Al- Najaf, which led to some areas adjacent to the Al-Bahar region. This creates a state of confusion in the subject of future planning for land uses within the study area. To examine this problem in practice, the images of the Sentinel-2 satellite (within the period 2016-2020) were selected. The resulted thematic maps included six classes of land use and land cover LULC, these classes are (agricultural areas, built up areas, gypsum soil, clay soil, sandy soil, and water areas). With regard to the accuracy of the performed classification process, the so-called confusion matrix indicates that the overall classification accuracy is about 85%. The study concluded that some of the important land use, both the road pilgrimage, the strategic line and its oil transfer accessories had been overwhelmed by water, as well as water approaches a newly built residential complex near the Bahar Al- Najaf. It is imposed by the study; the federal and local government agencies must take rapid measures and procedures to avoid potential future flood risk.